EVALUATING THE FACTORS INFLUENCING POULTRY FARMERS’ PARTICIPATION IN EGG PRODUCTION: A BINARY LOGIT REGRESSION MODEL - Jatto, N. A.; Maikasuwa, M. A.; Kyiogwom, U. B.; Muhammad, I. (European Scientific Journal, ESJ, 2012)
Insufficient information on the determinant of poultry farmers’ interest in egg production often limits the opportunity to predict the level of preference for poultry production. To develop policies in addressing poultry farmers’ problem in respect of their participation in egg production, the determinants and the level of their interest in agriculture have to be adequately explored and understood. Towards this end a study has been conducted in Ilorin, Kwara state capital to evaluate the factors influencing poultry farmers’ participation in egg production. The study area was divided into three and a stratified random sampling technique was adopted in selecting a total sample size of 300 respondents, out of which 50 registered poultry egg producers and 50 registered poultry non egg producers were selected from each division. A structured questionnaire was administered to obtain the information needed from the sampled producers. Data analysis was done using binary Logit regression. The result revealed that year of education, Farm size, income, participation in cooperative society and credit are the significant factors contributing to their participation. The marginal probability done on the significant binary Logit regression showed that participation in cooperative society had highest influence on the poultry egg farmer’s interest and credit access showed the extent of their interest in the elasticity of probability. The study concluded that socioeconomic variables such as years of education, farm size, income, participation in cooperative society and access to credit are the determinant of poultry egg farmer’s interest in egg production. It was recommended that Credit which had a positive and significant effect on the interest of poultry egg farmers is necessary to encourage technical innovations and timely availability of necessary inputs. Government should influence by reducing borrowing rates on credit in order to encourage and accelerate the transformation of poultry industry.